PCR based detection of Citrus yellow mosaic disease from Vidarbha region of Maharastra - KANCHAN BHANARE; V.K. BARANWAL, D.K. GHOSH,* BALAJI AGLAVE (Indian Phytopathology, 2007)
Citrus mosaic virus (CMBV),a non-enveloped bacilliform DNA virus measuring 130x30nm in size causes a severe mosaic disease of citrus particularly in sweet orange in southern India. Recent survey revealed the incidence of yellow mosaic disease in three commercial citrus cultivars viz. Nagpur mandarin, mosambi sweet orange and acid lime in central India. The disease incidence ranged from a maximum of 13.75 per cent in mosambi sweet orange as compared to 5.88 per cent in acid lime and 3.22 pel" cent in Nagpur mandarin in different citrus growing tracts of Vidharbha as diagnosed by PCR, electron microscopy and biodiagnosis. Since CMBV is weekly immunogenic, serodiagnosis is not a preferred diagnostic method. As an alternative, a rapid and reliable PCR based detection protocol has been standardized. Both commercially available DNeasy Plant minikit (Qiagen) as well as standard DNA extraction protocol with modification yielded good quality DNA from CMBV infected citrus leaves. By using two different set of primer pairs specific for partial polyprotein gene of CMBV genome, amplified product of expected sizes i.e. 726 bp and 245 bp have been successfully obtained from CMBV infected citrus leaf samples. PCR based detection is also confirmed by biodiagnosis and directly observing virus particle under electron microscope in leaf dip as well as partially purified preparation. This is the first authentic report on molecular evidence of CMBV incidence in all three commercial citrus cultivars of Vidarbha region of Maharashtra.